IMPLEMENTATION OF A PERFORMANCE APPRAISAL SYSTEM IN START-UP ZEAL INDONESIA - Evi Silvana Muchsinati; Syafira Nur Faatihah (ConCEPt - Conference on Community Engagement Project, 2022)
Zeal Indonesia is a start-up company that focuses on talent management which has been operating since 2018 with more than 60 employees. Currently, Zeal Indonesia actively offers careers opportunity and development through an internship program. The internship lasts for three to four months with remote working (work from home) system. The current number of interns is 29 people who occupy different positions. Even though they have dozens of employees, Zeal does not yet have an employee performance appraisal system to monitor the performance of its employees. Therefore, this project aims to assist Zeal Indonesia in implementing a performance appraisal system to monitor the interns' performance during the internship period. The author used interviews, observations, questionnaires, and company documents to gather empirical information regarding the needs of implementing an employee performance appraisal system. This performance appraisal system uses a graphic rating scale method with Google Forms and Google Spreadsheet to collect the data. With the implementation of this employee performance appraisal system, management can assess job behaviour, competencies, skills, and performance result of the interns. This performance appraisal will help the interns understand their values in the workplace. Thus, the improvement of their performance and development of their abilities and skills can be seen through time. Further research is expected to be able to implement a performance appraisal system in other types of start-up companies with other methods such as 360 Degree